RISKS OF THE INNOVATIVE PROJECT - Vasily Tur (Вестник Северо-Кавказского федерального университета)
In article concepts of innovative risk are analysed; risk management tasks in innovative activity are considered; the factors defining risks of innovative projects are systematized; stages of implementation of the innovative project are defined; the curve of dynamics of a cash flow at various stages of implementation of the innovative project is offered.